Digitalization of the KARI and KARA Web-based Financial Recording Systems to Improve Financial Literacy of Mulia Prasama Danarta Cooperative Members - Andre Kurniawan Pamudji; Stephani Inggrit Swastini Dewi; Ridwan Sanjaya (Journal of Innovation and Community Engagement, 2026)
Mulia Prasama Danarta Savings and Loan Cooperative is committed to improving the economic welfare of its members through financial literacy programs, one of which is the Budget Card (KARA) and Daily Card (KARI) methods. However, the implementation of these methods was still done manually using paper, making it inefficient, vulnerable to data loss, and unable to provide automatic financial analysis. This community service activity aimed to design and implement a web-based financial recording system to digitize the KARI and KARA methods, making it easier for members to plan budgets and record daily transactions. The implementation method for this activity utilized a participatory approach that included four stages: (1) survey and needs analysis, (2) website platform development, (3) dissemination and training attended by 50 members on July 28, 2025, and (4) impact evaluation attended by 27 members on September 11, 2025. Feedback data collection was carried out through an online questionnaire. The results of the activity show that the digital platform was successfully developed according to needs and was very positively received by members. Evaluation data shows that 92.6% of users intend to continue using this system because it is considered easy and useful. In addition, constructive feedback was obtained for future feature development, such as budgeting period flexibility. It was concluded that digitizing the KARI and KARA systems through a website platform is an effective solution with significant potential to increase the effectiveness of cooperative financial literacy programs and encourage better financial management practices for MSME members and individuals.